2019
DOI: 10.1002/hpm.2785
|View full text |Cite
|
Sign up to set email alerts
|

A spatio‐temporal cluster analysis of technical efficiency in the production of outpatient maternal health services and its structural correlates in México

Abstract: Summary Objective To analyze the formation of spatial clusters of technical efficiency (TE) in the production of outpatient maternal health services in México for the period 2008 to 2015. Methods We performed a longitudinal analysis of administrative and structural data related to the 243 Mexican health jurisdictions. We use window data envelopment analysis and spatial and econometric techniques. Structural correlates of each TE cluster obtained were identified estimating a pooled multinomial logit model. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, data envelopment analysis (DEA) is commonly used to measure the efficiency of PHCIs. The selected input variables mainly include operating costs and the number of administrative and technical personnel and beds, whereas the output variables mainly include the number of outpatients, referrals, hospitalizations, family services, and preventive health services (9)(10)(11)(12). Results of these studies revealed a generally low PHCIs efficiency and large efficiency differences across regions.…”
Section: Role Of Phc In Health Systemmentioning
confidence: 99%
“…On the other hand, data envelopment analysis (DEA) is commonly used to measure the efficiency of PHCIs. The selected input variables mainly include operating costs and the number of administrative and technical personnel and beds, whereas the output variables mainly include the number of outpatients, referrals, hospitalizations, family services, and preventive health services (9)(10)(11)(12). Results of these studies revealed a generally low PHCIs efficiency and large efficiency differences across regions.…”
Section: Role Of Phc In Health Systemmentioning
confidence: 99%